Carlos Aguirre y la intimidad como medio de expresión - Gastaldi, Marcelo (Universidad Nacional del Litoral, 2020)
The approach that this article proposes to take on the work of Carlos Aguirre will be from a collateral and, at the same time, paradoxical angle. On the one hand, the notion that intimacy operates as a channel of communication, in relation to language, will be worked on. On the other hand, the concept of intimacy will be considered as an «internal territory» that needs to be reaffirmed externally. By analyzing selected pieces, it will be seen how, ultimately, intimacy in Aguirre's work is manifested mainly through the titles, textuality and staging during concerts. In addition, an articulation between simple and clear melodies, song-like textures and the same conceptual idea will be perceived. Intimacy becomes a way of conceiving the work.